(untitled) (Theoretical and Applied Forestry, 2023)
This review article was carried out on Carob (Ceratonia siliqua L.), one of the secondary forest tree species that has an important place in our country’s forestry despite its limited distribution area. Carob has a high potential as a non-wood forest product. Within the scope of the study, the socio-cultural, economic and silvicultural characteristics of the species were examined. For example, in our country, 16,256 tons of carob fruits were produced in an area of ​​7,652 decares in 2019. According to the Carob Action Plan, it is stated that approximately 30,000 hectares of land in Mersin, Adana, Antalya, Kahramanmaraş and Muğla Regional Directorate of Forestry can be subject to Carob rehabilitation. Due to the properties and economic importance of carob, its usage area is increasing day by day.